The Juridical Review of the Position of the Deed of Sale and Purchase Signed by the Parties Not Before the PPAT - Danang Irfan Feriansyah; Taufan Fajar Riyanto (Sultan Agung Notary Law Review, 2022)
This study aims to find out and analyze the Juridical Review of the position of the sale and purchase agreement signed by the parties not carried out before the PPAT, as well as what are the legal consequences of the sale and purchase deed signed by the parties not before the PPAT on the PPAT. The research approach method used is a normative juridical research method. The research specification used is Descriptive Analysis. The data needed includes Primary data, which consists of the 1945 Constitution of the Republic of Indonesia, Government Regulation No. 24 of 2016 amendments to Government Regulation Number 37 of 1998, Regulation of the Minister of Agrarian Affairs of the National Land Agency Number 3 of 1997 concerning provisions for implementing Government Regulation Number 24 of 1997, Civil Law, as well as secondary data containing books and other supporting documents. Collecting research data using document study techniques and library materials. Methods of data analysis using Interactive Model Qualitative Analysis. Based on the research, it was concluded that the position of the deed of sale and purchase that was signed not before the PPAT, the strength of legal evidence is degraded to legal force under the hands and the sale and purchase deed signed by the parties is not before the PPAT, the PPAT can be subject to office sanctions, namely dismissal in disrespect of his position.